Collaboration between Residents and the Government of Kapanewon Purwosari through Land Utilization: Perspectives on Social Capital in Kacangan Hamlet, Gunungkidul - Salsabila Aurielia Putri; Eva Aulia Putri; Agustina Tri Wijayanti; Rusyda Nasyita Rahman (Program Studi Pendidikan IPS Unesa, 2026)
This study aims to analyze the collaboration between the community of Dusun Kacangan and the Purwosari sub-district government in land utilization based on social capital and its implications for social studies (IPS) learning. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. Informants were selected purposively, consisting of the village head and a neighborhood leader as key actors. Data were analyzed using reduction, coding, and thematic conclusion drawing, with source triangulation applied for validation. The results show that collaboration operates through three main mechanisms: participatory deliberation, a land auction system, and collective work (gotong royong). High levels of trust and open communication are key factors supporting the collaboration. Government support, such as the provision of agricultural inputs and the development of farm roads, strengthens program sustainability. These findings contribute to social studies learning by providing contextual learning resources to understand social interaction, community participation, and communitybased development.